2020
DOI: 10.1038/s41598-020-72843-5
|View full text |Cite
|
Sign up to set email alerts
|

Elk population dynamics when carrying capacities vary within and among herds

Abstract: Population and land management relies on understanding population regulation and growth, which may be impacted by variation in population growth parameters within and among populations. We explored the interactions between variation in carrying capacity (K), intrinsic population growth rate (r), and strength of density dependence (β) within and among elk (Cervus elaphus) herds in a small part of the geographic range of the species. We also estimated stochastic fluctuations in abundance around K for each herd. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 44 publications
(94 reference statements)
0
8
1
Order By: Relevance
“…Here, the strength of intraspecific density dependence decreased as the intrinsic growth rate of the focal species increased, which is contrary to the results of many previous studies in which the strength of intraspecific density dependence increased as the intrinsic growth rate increased (Lillegård et al 2008;Zehnder & Hunter 2008;Pasinelli et al 2011;Roy et al 2016;Gamelon et al 2019;Koetke et al 2020). On the other hand, a few studies have shown a negative relationship between environmental suitability and the strength of density dependence (Agrawal et al 2004;Lines et al 2020).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Here, the strength of intraspecific density dependence decreased as the intrinsic growth rate of the focal species increased, which is contrary to the results of many previous studies in which the strength of intraspecific density dependence increased as the intrinsic growth rate increased (Lillegård et al 2008;Zehnder & Hunter 2008;Pasinelli et al 2011;Roy et al 2016;Gamelon et al 2019;Koetke et al 2020). On the other hand, a few studies have shown a negative relationship between environmental suitability and the strength of density dependence (Agrawal et al 2004;Lines et al 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…First, this framework cannot be applied to situations in which invasion has failed in order to evaluate the causes, because it requires that both target species can be continuously observed. Second, the relationship between the strengths of intra-and interspecific density dependence and the intrinsic growth rates indicates pattern but not processes, because differences in intrinsic growth rates among localities will be multicausal phenomena, as suggested by the inconsistent relationship between strength of intraspecific density dependence and intrinsic growth rate in various studies (e.g., Agrawal et al 2004;Lillegård et al 2008;Zehnder & Hunter 2008;Pasinelli et al 2011;Roy et al 2016;Gamelon et al 2019;Koetke et al 2020;Lines et al 2020). Compared with the framework proposed here, future work should focus on the integration of this framework with the environmental gradient approach, which could be helpful for interpreting the mechanism underlying the pattern between strength of intraspecific density dependence and intrinsic growth rate through decomposing the effect of each environmental component.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent set of studies by Koetke et al . [ 54 ] found that the effect of political ideology on social distancing was moderated by trust in science, whereby conservative participants were more likely to social distance when they also reported higher trust in science. Thus, there appears to be interactive effects between political beliefs/affiliations and scientific trust that predict incremental variance in COVID-19 related behaviors, such as social distancing.…”
Section: Discussionmentioning
confidence: 99%
“…Predators of elk are mountain lions (Puma concolor) and black bear (Ursus americanus). Neither predator appears to exert much top-down influence on elk population dynamics in the parks [19,20].…”
Section: Study Areamentioning
confidence: 99%
“…This setting makes it feasible to reliably estimate the bulk of the food supply. Across the 15 years of our study elk abundance varied 3.9-fold and density dependent population dynamics were evident, implying negative feedbacks between elk abundance and the food supply [19][20][21]. Herein, we measured elk abundance, precipitation, and forage biomass at two spatial scales across 15 years in winter which is early in the growing season in this temperate rainforest.…”
Section: Introductionmentioning
confidence: 99%